Determinant of inequality in cesarean delivery in India: A decomposition analysis. Issue 7 (2nd July 2020) - Panda, Basant Kumar; Nayak, Itishree; Mishra, Udaya S.
Abstract: In India, Cesarean Section (CS) rate had got doubled in the last decade, with widespread diversity across the population subgroup. Hence, this study examined the pattern, inequality and driving correlates of CS in India. The attributes that shape the inequality in CS were private health facility, followed by the richest economic status, southern region, highest education level. A substantial rise in CS in private sectors and richer section raises the apprehension as to whether commercial motive of private providers contributes to the undue rise in CS that need not necessarily be genuine.